ЖИСМОНИЙ МАДАНИЯТ ФАНИНИ ЎҚИТИШНИНГ ДОЛЗАРБ МУАММОЛАРИ - Аҳмедов, Ф.Қ.; Кулбоев, Н.С.; Кўлдошев, С.Ф. (SCIENCE and SOCIETY, 2020)
The article focuses on the role and importance of the subject of physical culture in the education system, its functions aimed in educating the individual not only physically but also comprehensively.
Keywords: physical culture; education system; type of education; up-brining; subject; teaching; society; personality; harmonious human - being; upbringing; culture; human values